2010
DOI: 10.1002/clen.200900165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Azo Dye Concentration and Biomass Acclimation on Sludge Digestion and Dye Co‐treatment

Abstract: The effect of a reactive azo dye (the hydrolyzed form of Reactive Orange 107, HRO107) on the digestion of municipal waste sludge (WS) was studied. The study also focused on the effect of acclimation of the anaerobic mixed culture on dye treatment. Anaerobic batch assays were carried out in serum bottles under mesophilic conditions. Unacclimated and acclimated anaerobic mixed cultures were used for the study. Both unacclimated and acclimated anaerobic cultures completely reduced HRO107 during WS digestion. Inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Azo dyes characterized by the presence of one or more azo groups (eN]Ne) are extensively used as coloring agents in textile, leather, additives, foodstuffs, cosmetics and paper industries where a significant proportion of used dyes is disposed into the environment through wastewater (Banat et al, 1996;Jadhav et al, 2007;Pandey et al, 2007;Stolz, 2001). The chemical stability of azo dyes makes them relatively resistant to biological and chemical degradation processes and therefore, causes disposal problems in dye industries (Banat et al, 1996;Ozkan-Yucel and Gokcay, 2010). The discharge of dye-containing wastewaters in the environment causes both environmental and public health risks because of the negative ecotoxicological effects and bioaccumulation in wildlife (Chung and Stevens, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes characterized by the presence of one or more azo groups (eN]Ne) are extensively used as coloring agents in textile, leather, additives, foodstuffs, cosmetics and paper industries where a significant proportion of used dyes is disposed into the environment through wastewater (Banat et al, 1996;Jadhav et al, 2007;Pandey et al, 2007;Stolz, 2001). The chemical stability of azo dyes makes them relatively resistant to biological and chemical degradation processes and therefore, causes disposal problems in dye industries (Banat et al, 1996;Ozkan-Yucel and Gokcay, 2010). The discharge of dye-containing wastewaters in the environment causes both environmental and public health risks because of the negative ecotoxicological effects and bioaccumulation in wildlife (Chung and Stevens, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Parshetti et al reported that Kocuria rosea was able to decolorize 10 mg L −1 of methyl orange (100%) within 48 h, 30 mg L −1 in 60 h, and 100 mg L −1 in 120 h. Wang et al also observed that the time required for decolorization process increased with an increase in dye concentrations. Ozkan‐Yucel and Gokcay reported that under anaerobic condition both un‐acclimated and acclimated anaerobic cultures completely reduced reactive azo dye and the inhibitory concentration was found to be <800 mg L −1 . Similar results were also observed in the studies of Çinar et al , the increase in air supply decreased the decolorization of remazol brilliant violet 5R.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a single coagulation process is not an efficient method for azo dye removal because it takes a longer time and a higher amount of coagulation, as compared to the combination of oxidation and coagulation by ferrate. Oxidation by NaOCl was completed in 5 min at all pH conditions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and there was no further OD degradation during the remaining period (up to 30 min). In addition, a single coagulation process generates colored coagulated solid wastes, which may result in the toxicity of the sludge produced and an increase in total dissolved solids in the treated wastewater [26].…”
Section: Dye Removal Rate By K 2 Feo 4 and Naoclmentioning
confidence: 92%
“…Several approaches have been used for the removal of azo dyes from industrial wastewater. A combination of aerobic and anaerobic processes is carried out on dye effluent because it is cheap and easy to process; however, it is insufficient to remove hazardous particles from dye wastewater [8] Biological processes, including adsorption by microbial biomass and microbial degradation [9] are not effective for all dyes because of the stability, high water solubility, and high molecular weight of azo compounds [10]; furthermore, they tend to generate toxic byproducts [11,12]. In particular, azo dyes cannot be effectively treated by conventional biological processes because they are chemically stable [13].…”
Section: Introductionmentioning
confidence: 99%